DISKURSUS IDENTITAS PEREMPUAN DALAM MAJALAH PEREMPUAN MUSLIM INDONESIA - Nisa Kurnia Illahiati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
This study aims to critically analyze the female identity discourse articulated by the Indonesian Muslim Women’s magazine. Preceded by the emergence of a significant problem during the process of modernization, Indonesia has experienced the transformation of religious values from ideology toward commercialization of spirituality reflected in their lifestyle. The constellation of media discourse creates a meaning transformation on how identity is performed and how a Moslem is in contemporary Indonesia. This study applies a discourse analysis perspective by Michael Foucault. The data were gathered from a collection of visual and textual discourse obtained from three Moslem women’s magazine, Alia, Ummi and Noor. The data analyzed include pictures, words, and phrases as a marker of female identity as a Moslem. The results of this study indicate that the female identity as a Moslem in Indonesia is not an absolute thing. Even though the teaching is from the same scripture, the interpretation of female identity, its nature and its realm becomes plural as there was a lot of discussion and arguments Permalink/DOI: dx.doi.org/10.17977/um015v45i12017p086